2004
DOI: 10.1037/0735-7028.35.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Training Directors' Views of Trainees' Readiness to Practice Independently.

Abstract: When are psychology trainees ready to practice independently? This question has been debated extensively during the past few years. To contribute to this debate, a national survey of training directors of academic programs, predoctoral internships, and postdoctoral fellowships was conducted. The study explored training directors' views regarding the examinations and supervisory hours necessary to become an independent practitioner. The study found that training directors were divided in their opinions of when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
(21 reference statements)
0
22
0
1
Order By: Relevance
“…Common practice among examiners is to assign marks upon hearing students articulate key concepts in response to specific questions in a manner that shows competency and understanding. Earlier research suggested that competencies of students in professional psychology must be clearly articulated to aid evaluation (Rodolfa, et al, 2004). Of course, it is important to note that, while the present analysis concerned interrater reliability, no study of the validity of the examination, a considerably more complex task, was done.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Common practice among examiners is to assign marks upon hearing students articulate key concepts in response to specific questions in a manner that shows competency and understanding. Earlier research suggested that competencies of students in professional psychology must be clearly articulated to aid evaluation (Rodolfa, et al, 2004). Of course, it is important to note that, while the present analysis concerned interrater reliability, no study of the validity of the examination, a considerably more complex task, was done.…”
Section: Discussionmentioning
confidence: 97%
“…Of course, while the results indicate very acceptable interrater reliability, they provide no information on validity. It is the issue of validity of oral examinations that seems to have led some states in the USA to question the usefulness of an oral examination as a measure of competency to practice (Rodolfa, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, postgraduate education is available in the Republic of Ireland in the following applied psychology sub-disciplines: clinical, counselling, forensic, health, educational, and organisational psychology, many of which are now available at doctoral level (for example, clinical, counselling and educational psychology). While research doctorates may be pursued in a number of areas in psychology, there is a growing international interest in applied programmes in psychology (Karandashev 2008 Although a number of different education models inform the education of psychologists, they all attest to the need for research to inform practice (Cheasty, Clare, and Collins 1998;Goodheart and Carter 2008;Hunsley 2007) and to the need for integration of science and practice in applied psychology (Borden and Ilvried 2008;Neimeyer and Goodyear 2005;Rodolfa, Ko, and Petersen 2004). The model that has been widely adopted within the profession is more commonly referred to as the 'Scientist-Practitioner' model (Cheshire and Pilgrim 2004;Huey and Britton 2002).…”
Section: Psychology Education and Trainingmentioning
confidence: 99%